Editorial - Thomas Wilson (Information Research: An International Electronic Journal)
Our adoption of OJS to manage the full production process of the journal continues to progress, with expected and unexpected glitches here and there, which Tobias Carlsson and Ty Nilsson cope with very effectively.  Tobias is leaving us for a new job and we wish him well.